Sofrimento psicológico e fatores associados em universitários da área da saúde de Rio Verde, GO, Brasil - Cruvinel, Érica Alves Pereira (Universidade do Vale do Rio dos Sinos, 2023)
Objective: To investigate the factors associated with psychological suffering in university students in the healthcare area of “Universidad de Rio Verde - UniRV, Goiás”. Method: A university-based and cross-sectional study included 2,237 university students that have completely answered the psychological distress screening instrument by Kessler Psychological Distress Scale (K10) of both genders and aged ≥ 18 years. Were considered as dependent variable, having regard to the presence of psychological distress; and as independent variables, demographic, socio-economic, academic aspects, and of health-related behaviors that there have been associated with psychological distress. Gross and adjusted prevalence ratios and respective 95% confidence interval (95%CI) were estimated through the Poisson regression with robust variance in STATA version 15. Only variables with lower than 20% (p<0.20) significance in bivariate analysis were taken to the adjusted analysis, which was conducted made from blocks. Were considered factors associated with psychological distress variables with significance level of at least 5%. Results: Whereas the information collected, we could notice that the overall prevalence of students with psychological distress high/very high level were 68% of prevalence (95%CI= 1.66-1.70). In the adjusted analysis, which variables affect the student’s psychological distress high/very high level, were female gender (RP=1.10; 95%CI= 1.07-1.13), education in medicine (RP=1.04; 95%CI=1.01-1.07), smoker or former smoker (RP=1.05; 95%CI=1.02-1.08), sedentary lifestyle (RP=1.04; 95%CI=1.01-1.07), poor/very poor quality of life (RP=1.14; 95%CI=1.11-1.18) and being or not physically active (RP=1.05; 95%CI=1.01-1.08). The fact of be aged 25 years or over (RP=0.93; 95%CI=0.90-0.97) demonstrate the potential for protective factor of psychological distress. Conclusion: The high prevalence of mental suffering found among students in the health area is discussed in the light of aspects related to mental health assessment, gender differences and health promotion strategies in the university context.
Keywords: Sofrimento psicológico; Estudantes; Estudos transversais; Psychological distress; Students; Cross-sectional studies; ACCNPQ::Ciências da Saúde::Saúde Coletiva